Community-driven strategies for sustainable resource management, pollution control, and renewable energy transition in the Asia-Pacific - Ash-Shiddiqie, Luqman (Energy Justice, 2025)
Background: Environmental degradation in the Asia-Pacific region, driven by rapid urbanization, deforestation, overfishing, and unsustainable resource use, threatens biodiversity and local livelihoods. Community-based Conservation (CBC) initiatives play a crucial role in addressing these challenges while advancing Sustainable Development Goals (SDGs), particularly SDG 6 (clean water and sanitation), SDG 7 (affordable and clean energy), SDG 11 (sustainable cities and communities), and SDG 14 (life below water). Methods: This study uses a Systematic Literature Review (SLR) to analyze the contribution of local communities to sustainable development in Asia-Pacific, focusing on air conservation, renewable energy, urban aspirations, and marine conservation. Data were obtained from verified journals and reports (2011–2023), analyzed thematically to identify challenges, successful strategies, and opportunities in community-based initiatives. Findings: CBC initiatives have demonstrated success in improving environmental conditions and socio-economic well-being. Local communities effectively leverage their ecological knowledge to implement conservation strategies, leading to better resource management and ecosystem restoration. However, financial and technical constraints remain key challenges to the scalability and long-term sustainability of these projects. Conclusion: Addressing financial and technical barriers is essential for expanding CBC initiatives. Strengthening policy integration and multi-level governance—through collaboration between local communities, national governments, and international organizations—can enhance institutionalization and long-term sustainability. These efforts are critical for promoting resilience against climate change and other environmental threats in the Asia-Pacific region. Novelty/Originality of this article: This study highlights the intersection of traditional ecological knowledge and modern conservation strategies in CBC initiatives. It underscores the importance of policy integration and multi-level governance in ensuring the success and scalability of community-driven conservation efforts, contributing to sustainable development and climate resilience in the Asia-Pacific region.